Target status and method of payment : a perfomance analysis of acquisitions in Malaysia / Lee Siew Peng - Lee, Siew Peng (2010)
This study investigates firms performance in acquisition based on the target status and methods of payment in the Malaysian market over the period 2000-2004. To measure the acquiring and target firms abnormal returns around the acquisition announcements, the study employs the market model with Scholes-Williams adjustments for thin trading. For long-term analysis after acquisition, we use the market-adjusted model and buy-and-hold abnormal approach. The study finds that, in the short-term, acquisition activities create positive gain to both acquiring and target firms, most of which go to the target firms. Further, most of the abnormal returns occurs on day 0 and day 1. This is consistent with a market efficiency situation in which the information content of the acquisition announcement is quickly incorporated into the share prices. However, contrary to most of the earlier findings, this study finds that the low value creation in the acquiring firms becomes significantly negative when it involves acquisition of unlisted private target firms. We reasoned that this is primarily due to the strong bargaining power of the acquired firms since the private targets in Malaysia are typically family-owned or closely held by a limited number of shareholders. It is also found that after controlling for the methods of payment, both the acquiring and target firms in cash offers receive higher gain than share offers. Despite the general belief that acquirers of private targets gain more when share offer is used, this study finds an opposite result. This may be due to the size of the private targets being very small relative to the size of the acquiring firms. Hence target shareholders would not be able to effectively monitor post-acquisition activity of the acquiring firms. Further, the relative size of target to acquiring firm suggests that the larger the target the greater the acquirer’s returns. The overall results support the financing signaling hypothesis that sharesettlement is viewed negatively by the market regardless of the target status. As for the long-term post-acquisition analysis, evidence reveals that acquiring firms experience wealth losses for three years regardless of the target status and method of payment. This might indicate that market overreacted to the acquisition announcement. Further analysis reveals that the significant underperformance is only prevalent for acquirers of unlisted private targets regardless of method of payment, and for acquirers using share-settlement regardless of target status. When controlling for firm size, book-to-market ratio the results suggest that underperformance may limited to small size acquirers and acquirers with high bookto- market ratio. Further, this study report acquirers returns are not sensitive to the different models of excess return estimation employed.